Apelin receptor inhibition in ischemia-reperfused mouse hearts protected by endogenous n-3 polyunsaturated fatty acids - Zheng, Shuang; Tan, Weijiang; Li, Xiang; Wang, Lijing; Zhu, Caiyi; Pyle, W. Glen; Chen, Jianxin; Wu, Jian; Ren, Xuecong; Chen, Honghua; Zou, Yunzeng; Backx, Peter H.; et al. (Frontiers in Pharmacology, 2023)
Background: While the protective effects of n-3 polyunsaturated fatty acids (PUFAs) on cardiac ischemia-reperfusion (IR) injury have been previously reported, limited data are available regarding how these fatty acids affect membrane receptors and their downstream signaling following IR injury. We aimed to identify potential receptors activated by n-3 PUFAs in IR hearts to understand the regulatory mechanisms of these receptors.We used fat-1 mice, which naturally have elevated levels of n-3 PUFAs, and C57BL/6J mice as a control group to create a myocardial IR injury model through Langendorff perfusion. We assessed the impact of endogenous n-3 PUFAs on left ventricular function, myocardial infarct size, myocardial apoptosis, and ATP production. RNA-seq was conducted to predict and verify the receptor affected by elevated endogenous n-3 PUFAs. We then treated IR hearts of WT and fat-1 mice with an antagonist or an agonist for the predicted receptor to assess cardiac contractile function and intracellular signaling pathways. An in vitro hypoxia-reoxygenation (HR) was also used to confirm the effects of n-3 PUFAs on the examined intracellular signaling pathways.Results: Endogenous n-3 PUFAs protected cardiac structure and function in post-IR hearts, leading to alterations in three phosphorylation signaling pathways. RNA-seq analysis revealed that n-3 PUFAs affected multiple biological processes and suggested that they inhibited the apelin receptor (APLNR). Consequently, ML221 synchronized the activation of the PI3K-AKT-mTOR signaling axis, suppressed the expression of PKCδ and phosphorylated p38α, upregulated or restored the phosphorylation of myofilaments, and prevented myocardial injury and contractile dysfunction in WT IR hearts. Furthermore, apelin-13 disrupted the PI3K-AKT-mTOR signaling axis in post-IR fat-1 hearts. The phosphorylation signaling targeted by APLNR inhibition in post-IR fat-1 hearts was also observed after treating HR cells with EPA. Endogenous n-3 PUFAs protect against post-IR injury and preserve cardiac contractile function through APLNR inhibition. This inhibition synchronizes the PI3K-AKT-mTOR axis, suppresses detrimental phosphorylation signaling, and restores or increases myofilament phosphorylation in post-IR hearts. The beneficial effects observed in fat-1 transgenic mouse hearts can be attributed, at least in part, to elevated EPA levels. This study is the first to demonstrate that n-3 PUFAs protect hearts against IR injury through APLNR inhibition.